Influence of voluntary action and outcome valence on the sense of agency - Niu, Nana; Wu, Yun; Li, Hui'e; Li, Mei; Yang, Danping; Fan, Wei; Zhong, Yiping (Frontiers in Human Neuroscience, 2023)
Recent studies have revealed that people might experience a lessened sense of agency for negative consequences by claiming that they were obeying orders. However, little is known about the cognitive neural mechanism behind the reduced sense of agency when individuals are forced to inflict physical harm on others. This study adopted temporal estimation tasks to investigate the internal mechanism of voluntary action on the sense of agency and the moderating effect of outcome valence as measured by event-related potentials (ERPs). In the temporal estimation task, participants were asked to make trade-offs of monetary gains for themselves against painful electric stimuli experienced by strangers, subjectively estimated the perceptual temporal interval between keypress actions (i.e., free or coercive actions) and consequent outcomes (i.e., positive or negative tones) and rated the feeling of control. The results showed that perceived temporal interval was shorter for positive tones compared with negative tones in the coercive condition, and induced more negative N1 and N300 amplitudes, which indicated that the implicit sense of agency was higher. However, the explicit sense of agency was stronger in the free condition than in the coercive condition, which was not influenced by outcome valence. We discuss the implications of utilizing positive feedback and free choice as significant strategies for those experiencing the abnormal sense of agency.